THE EFFECT OF PAKEM METHODS AND LEARNING MOTIVATION TOWARDS EIGHT GRADE STUDENT’S LEARNING OUTCOMES ON IPS at SMP PGRI 2 MUNCAR BANYUWANGI - Marsitin, Marsitin (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2023)
This study is a causal, quantitative research are : 1) Is there any influence on learning outcomes ?, 2) Is there any influence of learning motivation to ward student learning result ?, and 3) Is there any interaction influence of PAKEM) learning and learning motivation to ward student learning result ? Objectives : 1) The examine the impact of PAKEM learning on student learning outcomes. 2) examine the effect of learningmotivation on the student learning outcomes. 3) examine of the influence of PAKEM learning motivation on student learning outcomes. The population of this studied in this research is the students of SMP PGRI 2 Muncar distric Banyuwangi, with the number of 30 student, the research area is determined by purposive sampling method. The research is aquantitative research with causal design.Data collection tools use questionnaires, test and methods of documentationand intervew. Valid and valid realibility tools with validity and reliability tets. The instrument analysis test use :1) descriptive test, 2) normality test, 3) homogeneity test. Test the hypotesis by : 1) regression analysis, 2) F test, 3) t test,4) testcoefficient of determination (R2). The resultshowed that: 1) sig showed that: 1) sig value of learning variables PAKEM on studentlearning outcomes 0,000, conclusion sig>0,05, mean learning of PAKEM have signifficant effectto resultof studentlearning, 2) sig value of learning of motivation variable is 0,000, sig conclusion>0,05 this means learning motivation has a signifficant effecc on student learningoutcomes, 3) the output of regression analysis obtained F hitung 29,142 with sig. 0,000, because > 0,05 then there is interaction influence of learning of PAKEM and motivation learn earnestly to result learn